The Influence of Various Matrixes on the Strength Properties of Moulding Sands with Thermally Hardened Hydrated Sodium Silicate for the Ablation Casting Process - Major-Gabryś, Katarzyna; Puzio, Sabina; Bryłka, Agata; Kamińska, Jadwiga (Journal of Casting & Materials Engineering, 2021)
The essence of ablation casting technology consists in pouring castings into single-use moulds made from the mixture of sand and a water-soluble binder. After pouring the mould with liquid metal yet while the casting is still solidifying, the mould destruction (washing out, erosion) takes place using a stream of cooling medium, which in this case is water. This paper focuses on the selection of  moulding sands with hydrated sodium silicate for moulds used in ablation casting. The research is based on the use of water glass 145 and 150 as binders. As part of the research, loose moulding mixtures based on two silica sands from different sand mines with different content of binders were prepared. The review of literature data and the results of own studies have shown that moulding sand with hydrated sodium silicate hardened by dehydration is characterized by sufficient strength properties to be used in the ablation casting process. Our own research also confirmed the possibility of using these sand mixtures in terms of both casting surface quality and sand reclamation. The results presented in this paper prove that both sand grains and types of binder tested may be used as components in moulding sands devoted to ablation casting.